Novità sul segreto investigativo nel d.l. n. 161 del 2019 in tema di intercettazioni - Zampini, Andrea (Cultura giuridica e diritto vivente, 2020)
[Changes to the investigation secret in the “wiretaps” law decree no. 161 of 2019] After two years of numerous referrals in the wiretaps reform (legislative decree no. 216 of 2017), the government has decided to take on the matter with an emergency intervention (law decree no. 161 of 2019, which is currently awaiting its conversion in to law). Investigative secret is one of the various aspects faced by the decree. If compared to the 2017 reform, secrecy is confirmed in its perimeter in the authorization phase (art. 329 CCP) and reduced in its general duration (art. 269 CCP). Partly due to the well-known negligence of the legislator in law drafting techniques, these innovations show a legal system on which remain doubts because of its total inadequacy to grant at least minimum levels of guarantee for the fundamental rights involved.